2018
DOI: 10.15294/ujph.v7i1.17400
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Soil Transmitted Helminth Infection on Primary School Children

Abstract: Soil Transmitted Helminth (STH) infection is the third ranks of the top 10 common infectious diseases in the world, with an incidence rate about 1.4 billion per year. The incidence of STH in Indonesia is still quite high. Amount 60-80% of STH infection is occurs in primary school students, while 40%-60% infection for all ages. The purpose of this study was to determine factors related to STH infection in primary school children at Moyudan Primary School in Sleman Regency. This research conducted using an analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
1
8
0
2
Order By: Relevance
“…Cacingan adalah salah satu bagian dari masalah kesehatan masyarakat dan termasuk penyakit berbasis lingkungan dengan media penularan melalui tanah sehingga disebut dengan Soil Transmited Helminth (STH) (Martila, 2015). Sofiana (2011) menjelaskan bahwa infeksi cacingan ini dapat berpengaruh pada pertumbuhan dan perkembangan anak. Infeksi penyakit pada anak juga dapat mengakibatkan prestasi akademik menurun karena berhubungan dengan penurunan jumlah kehadiran siswa di kelas (Moonie, 2008).…”
unclassified
“…Cacingan adalah salah satu bagian dari masalah kesehatan masyarakat dan termasuk penyakit berbasis lingkungan dengan media penularan melalui tanah sehingga disebut dengan Soil Transmited Helminth (STH) (Martila, 2015). Sofiana (2011) menjelaskan bahwa infeksi cacingan ini dapat berpengaruh pada pertumbuhan dan perkembangan anak. Infeksi penyakit pada anak juga dapat mengakibatkan prestasi akademik menurun karena berhubungan dengan penurunan jumlah kehadiran siswa di kelas (Moonie, 2008).…”
unclassified
“…This result is accordingly but lower than the study conducted by Sofiana et al who also found Trichuris trichiura as the major type of STH infection with a proportion of 24.6%. 13 Other research in Karangasem region, Bali showed a varied prevalence of STH infection, namely a study in Gegelang Village found a prevalence of 31.7%, study in Antiga Kelod Village reported a prevalence of 24.8%, while research in Ngis Village depicted the prevalence of 10.1%. [7][8][9] The results of this study indicated that there was a significant relationship between frequently playing on soil with STH infection.…”
Section: Resultsmentioning
confidence: 96%
“…This result is supported by the study of Sofiana et al which showed that children who did not wash their hands had a risk of being infected with STH 2.23 times higher than children who washed their hands. 13 Sandy et al also reported that children who had bad hands washing habits (using water only) had 3.03 times higher risk to be infected by STH than those who had good hands washing habits (using water and soap). 17 Transmission of STH infections can pass through the skin pores of the feet.…”
Section: Resultsmentioning
confidence: 99%
“…often play in the ground and adults who work in the garden or the fields. Transmission of worm infection can be through long fingernails where there is a possibility that worm eggs tucked in so that the worm eggs swallowed when eating (11).…”
Section: This Condition Usually Occurs In Children Whomentioning
confidence: 99%